Use of multiple stress indices as a measure of heat tolerance in wheat accessions - Shehrawat, Sachin; Kumar, Yogender; Singh, Jogendra (Journal of Cereal Research, 2020)
Wheat is a crop of global significance, grown in diversified environments. Heat stress affects a number of morpho-physiological traits in crops including wheat. A set of 40 wheat accessions along with four checks were screened for heat tolerance based on various stress indices. The present study was undertaken during rabi 2018-19 in randomized block design having three replications at CCS Haryana Agricultural University, Hisar under two dates of sowing i.e. 24th November and 24th December. Significant variance was observed among genotypes based on HSI of all the traits except plant height and spike length. Based on HSI and TOL, the accessions DT 126, DT 46, DT 142, DT 102 and DT 124 were found to be most tolerant to heat stress, whereas on the basis of HRI, HTI, MP and GMP, the promising accessions identified were DT 116, DT 101, DT 181, WH 1124, HD 3059 and DT190. The accessions identified as heat tolerant would form an important resource for the development of high yielding varieties under heat stress condition. Correlation coefficients based on HSI of different traits revealed significant positive association of grain yield per plant with biological yield per plant, harvest index, NDVI 1, tillers per plant and 1000 grain weight, denoting that these traits can be used effectively, for selection of heat tolerant genotypes. Grain yield was found to be positively correlated with the indices viz., HRI, HTI, MP and GMP while, negatively with HSI and TOL under stress condition. The stress indices used under study were recognized as paramount for identifying cultivars with high tolerance to heat stress.